Colonic and gastric cancer metastatic lymph nodes: applications of autofluorescence-based techniques - Desiree Pantalone; Monica Monici; Giovanni Romano; Francesca Cialdai; Raffaella Santi; Franco Fusi; Camilla Comin; Paolo Bechi (Oncology Reviews, 2011)
Lymphadenectomy and extended lymphadenectomy are still controversial issues in surgical oncology. The detection methods for metastatic lymph nodes include lymphoscintigraphy and radiolabelled antibody, but immunohistochemical sentinel lymph node (SLN) identification is commonly used. The potential diagnostic use of cell and tissue autofluorescence (AF) is well known. Here we review our studies on the application of AF-based techniques for diagnosing metastatic lymph nodes. We had previously demonstrated that AF imaging allows discrimination between hyperplastic and primary neoplastic lymph nodes. Our more recent studies show that the combination of autofluorescence microspectroscopy and multispectral imaging autofluorescence microscopy can be applied to the diagnosis of secondary neoplastic lymph nodes in gastric and colorectal cancer. These techniques have been validated by histochemical and immunohistochemical methods. Studies are in progress to select the best dye tracer for SLN identification, to improve image quality and to develop a software for automatic analysis of tissue AF to help the decision-making process during surgery.